Intertemporal Efficiency Analysis on Indonesia Islamic Banks: A Window DEA Approach - Marlina, Lina; Sudana, Sudana; Rusydiana, Aam Slamet (Universitas Siliwangi, 2023)
Introduction to The Problem: Measurement of the level of efficiency of Islamic banks in Indonesia is widely carried out. But almost no one has done research with the DEA window analysis approach.Purpose/Objective Study: This paper aims to measure the efficiency of Islamic banks in IndonesiaDesign/Methodology/Approach: – Using Data Envelopment Analysis (DEA) method and window DEAFindings: This research shows that the efficiency of Islamic banks that included in observations from 2011-2016 fluctuated with a mean value of 63 percent. From the perspective of efficiency stability analysis through several summary statistics such as standard deviation (SD), Long Distance per Window (LDW), Long Distance per Period (LDP) and Long Distance per Year (LDY), the relatively stable Islamic bank efficiency value is Bank SyariahMandiri (BSM) and BCA Syariah.